Tooth Wear and Periodontal Status in a Cluster of Middle-Aged Adults in Northern Greece - Charis Theodoridis; George Menexes; Vasiliki Topitsoglou; Sotirios Kalfas (Hygiene, 2023)
The present observational study aims to investigate the prevalence of tooth wear (TW) in a cluster of Northern Greek adults aged 35–44 years and, additionally, to assess any probable associations and interrelationships between TW and periodontal condition and sociodemographic factors. A cross-sectional design was embraced identically to our previous study on senior citizens. A sample of 531 individuals was considered, and they were examined according to WHO guidelines for national pathfinder surveys by three calibrated dentists-examiners in different urban and rural areas of Northern Greece. Simplified Tooth Wear Index (TWI), Community Periodontal Index (CPI), Attachment Loss (AL) and simplified Oral Hygiene Index (OHI-S) were screened and calculated in a patient-level approach. TW is quite prevalent among middle-aged adults in Northern Greece, although it remains lower compared to older age groups. All the aforementioned periodontal indices were correlated significantly with TW; moreover, a tendency was detected for there to be more tooth wear in older age participants within the specific age group, in men as compared with women, in persons with lower educational levels and in those residing in rural areas.